Pembuatan Briket Komposit Cangkang Sawit dan Tempurung Kelapa dengan Variasi Perekat Tepung Tapioka sebagai Bahan Bakar Alternatif - Nurhamida Nurhamida; Rusdianasari Rusdianasari; Mustain Zamhari (Politeknik Negeri Lhokseumawe, 2023)
Waste from the agricultural sector in Indonesia that may be used as fuel is plentiful, but it is not well utilized by the community. The usage of wood charcoal fuel, which is extensively utilized as an energy source, would undoubtedly have a detrimental influence on the environment if used directly and constantly without passing through a particular process. Furthermore, as the consumption of oil and gas energy sources grows, the availability of oil and gas energy sources will become progressively reduced. This problem may be solved by converting it into ecologically beneficial charcoal briquettes and promoting the use of biomass waste in agriculture. Charcoal briquettes are an environmentally friendly source of biomass energy made by bonding mashed materials (such as sawdust, coconut shells, palm shells, rice husks, corn cobs, and other combustible materials) into solid blocks that are compressed under pressure using a binder in the form of tapioca flour solution. The purpose of this research is to evaluate the properties of composite briquettes made of palm kernel shells and coconut shell charcoal so that they may be utilized as alternative fuels to replace fossil fuels. The method used in this study is an experiment with qualitative analysis. Based on the results of the examination, the greatest proximate studied had the following characteristics: water content of 6.5%, ash content of 7%, flying substance content of 21%, and calorific value of 5448.1737 The findings obtained are consistent with the quality standards of charcoal briquettes established by SNI No. 01-6235-2000.